INVESTIGATION OF THE AMINO ACID COMPOSITION IN BLACK AND WHITE MULBERRY (MORUS NIGRA L. AND MORUS MULTICAULIS PERR.) VARIETIES - Zokirova, Mashhura; Gulomkhojaeva, Nargiza (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
This article presents a scientific analysis of the chemical composition and biological significance of mulberry fruits. It specifically focuses on the amino acid and flavonoid content of Morus nigra L. (black mulberry) and Morus multicaulis Perr. (black pearl mulberry) varieties grown in Uzbekistan. The compounds were identified using the high-performance liquid chromatography (HPLC) method. The obtained results are presented and analyzed in tables.